2016
DOI: 10.1177/1099636216652580
|View full text |Cite
|
Sign up to set email alerts
|

Sound transmission loss characteristics of sandwich aircraft panels: Influence of nature of core

Abstract: Sandwich panel which has a design involving acoustic comfort is always denser and larger in size than the design involving mechanical strength. The respective short come can be solved by exploring the impact of core geometry on sound transmission characteristics of sandwich panels. In this aspect, the present work focuses on the study of influence of core geometry on sound transmission characteristics of sandwich panels which are commonly used as aircraft structures. Numerical investigation has been carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…There have been several reported implementations and developments of the Rayleigh integral method [244][245][246][247][248][249][250][251][252][253][254], including vibro-acoustics [197,255,256]. Applications of the method include sandwich panels [257][258][259][260][261][262][263], engine or machine noise [203], electrostatic speaker [264] and transducers [52,265,266].…”
Section: The Rayleigh Integral Methodsmentioning
confidence: 99%
“…There have been several reported implementations and developments of the Rayleigh integral method [244][245][246][247][248][249][250][251][252][253][254], including vibro-acoustics [197,255,256]. Applications of the method include sandwich panels [257][258][259][260][261][262][263], engine or machine noise [203], electrostatic speaker [264] and transducers [52,265,266].…”
Section: The Rayleigh Integral Methodsmentioning
confidence: 99%
“…The results suggest that spatially random irregularities in honeycomb core have considerable effect on the natural frequencies of sandwich panels. MP Arunkumar et al [93] found that, for a honeycomb core sandwich panel in due consideration to space constraint, better sound transmission characteristics can be achieved with lower core height. Also, observed that, for a honeycomb core sandwich panel, one can select cell size as the parameter to reduce the weight without affecting the sound transmission loss.…”
Section: Sandwichmentioning
confidence: 99%
“…The STL of a sandwich panel depends on the characteristics of two surface layers, middle layer or core and supported boundary conditions. Arunkumar et al 13 studies the STL of a sandwich panel with a honeycomb core. The influences of the honeycomb shape and size on the STL at low and high frequencies are studied numerically.…”
Section: Introductionmentioning
confidence: 99%